Golden Dawn through a psychosocial lens - Dragonas, Thalia (Historein, 2016)
The economic and sociopolitical factors related to the current Greek crisis are translated into intrapsychic and interpersonal mechanisms in order to explain the political phenomenon of Golden Dawn. I draw on psychoanalytic concepts to reflect on how the crisis has functioned as a mechanism for the production and control of individual and collective subjectivities. I argue that the crisis has created immense insecurity and has fuelled feelings of desperation, fear and anger. For some, these feelings have been displaced onto a substitute reality offered by a transcendent group represented by Golden Dawn; personal boundaries have loosened, and subjectivities have been absorbed by a large, collective “false self”. At the centre of the notion of this substitute reality is the fantasy of omnipotence, channelled through the mechanism of projection onto the leader of the group. History is used and misused in order to cement the psychic life of the group and as a compensatory mechanism for the felt national shame. Moreover, collective denigration, or even extinction, of immigrants serves to displace negative feelings and impulses onto the “other”. I borrow Freud’s contention that when evil is not condemned, raw and wild impulses are let loose –hence, the assassination of a leftwing rapper that has landed Golden Dawn in court.